Cladistic analysis of the family Marginellidae (Mollusca, Gastropoda) based on phenotypic features - Souza, Paulino José Soares Jr.; Simone, Luiz Ricardo L. (Zootaxa, 2019)
As part of a project intended to review the taxa of Marginellidae worldwide, the phylogenetic relationships of its main representatives are provided based on comparative phenotypy. Characters from most structures and organs are investigated and used for a phylogenetic analysis, resulting in the following cladogram: ((((Marginellona gigas ((Eratoidea watsoni ((Prunum sp—Leptegouana guttata) (Volvarina brasiliana (Prunum prunum—P. rubens)))) (Austroginella muscaria (Marginella ealesae ((Marginella rosea (M. glabella—M. sebastiani)) (Dentimargo bruneolus (Eratoidea scalaris (Dentimargo sp—D. aureocincta)))))))) Pachycymbiola brasiliana*) Persicula sagitatta*) Buccinanops gradatus*). Those marked with * are outgroups functionally analyzed as part of the ingroup (respectively a volutid, a cystiscid and a nassariid); the root is based on Trophon geversianus (Muricidae). The genera Prunum, Marginella and Dentimargo are revealed as non-monophyletic. The monophyly of the family Marginellidae is supported by 17 synapomorphies. The volutids appear to be its sister taxon, and the possibility of Marginellidae being only a branch of Volutidae is discussed.